2021
DOI: 10.1111/vox.13125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of red blood cell transfusion on inflammation, endothelial cell activation and coagulation in the critically ill

Abstract: Background and Objectives: Red blood cell (RBC) transfusion is a frequently applied intervention in an intensive care unit. However, transfusion is associated with adverse outcomes including organ failure and thrombo-embolic events. Mechanisms of these effects are not known but may be related to activation of the endothelium or of the coagulation or inflammatory system. We hypothesized that a RBC transfusion in the critically ill would result in further activation of these systems. Materials and Methods:In 74 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Samples were collected in ethylenediaminetetraacetic acid (EDTA) tubes and centrifuged at 1500 g for 20 min, the plasma was then stored at −80°C until further analysis. Soluble syndecan‐1, IL‐6, and other biomarkers were analyzed within the prospective cohort using a custom designed human pre‐mixed multi‐analyte luminex assay as described by the manufacturer (Luminex R&D Systems Inc., Minneapolis, MN, USA) after data collection was finished 20 . NT‐proBNP, IL‐10, and IL‐8 were measured in EDTA plasma 4 years after completion of data collection using ELISA (R&D Systems Inc., Minneapolis, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were collected in ethylenediaminetetraacetic acid (EDTA) tubes and centrifuged at 1500 g for 20 min, the plasma was then stored at −80°C until further analysis. Soluble syndecan‐1, IL‐6, and other biomarkers were analyzed within the prospective cohort using a custom designed human pre‐mixed multi‐analyte luminex assay as described by the manufacturer (Luminex R&D Systems Inc., Minneapolis, MN, USA) after data collection was finished 20 . NT‐proBNP, IL‐10, and IL‐8 were measured in EDTA plasma 4 years after completion of data collection using ELISA (R&D Systems Inc., Minneapolis, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…There were 64 patients with all 3 blood samples present included in this study out of 74 patients that participated in the prospective study. 20 Three patients were excluded because of missing clinical data. Seven patients were excluded because of missing samples.…”
Section: Twelve Cases Out Of a Total Of 64 Were Identified As Taco Pa...mentioning
confidence: 99%
“…Another study found an increase in levels of von-Willebrand-factor antigen in critically ill patients receiving a RBC transfusion. The von Willebrand factor antigen has a causal role in the activation of endothelium and also in the development of thrombi formation [79]. After cardiovascular surgery, the levels of plasma tissue factor are persistent high for 30 days, which can increase the risk of VTE [80].…”
Section: Allogeneic Transfusion and Thrombosismentioning
confidence: 99%
“…Despite the large number of studies, their observational design hampers a conclusion of causality between PRBC transfusion and VTE. Mechanistically, most clinical situations requiring RBC transfusion are likely to have some level of coagulation activation and/or inflammation which might be enhanced following transfusion [71 ▪ ]. Both stored RBCs and sREVs can provide a procoagulant surface to enhance thrombin formation, although this activity may be proportionally higher with sREVs than RBCs in individual units [31].…”
Section: Potential Clinical Implications In Adverse Outcomes Of Blood...mentioning
confidence: 99%